DESIGN AND CONSTRUCTION OF A SAVONIUS TYPE L WIND TURBINE PROTOTYPE WITH OPEN VARIATIONS AS AN ELECTRIC ENERGY ALTERNATIVE FOR LIGHTING IN LIFT NET NORTH SEMARANG - Iqbal Naseem; Adi Kurniawan Yusim; Aulia Windyandari; Mohd Ridwan; Luthfansyah Mohammad (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2024)
This study investigates wind speed, wind turbine design to be implemented on fixed lift net in the waters of North Semarang in fishing with the help of lights. The research was carried out by designing and making a prototype of a Savonius type L wind turbine with a blade diameter of 400 mm and a height of 400 mm which was carried out directly on the beach for 10 hours and tested with a blue light to produce fish catches on the fixed lift net. The results of the use of blue lights were obtained from seven types of catfish, anchovies, Rebon fish, Selar fish, Cucut fish, mullet and layur fish with a total catch of 125.16 kg. The results obtained from processing wind turbine data are that the generator power at a wind speed of 1.3 m/s is 0.896 W, the highest power at a speed of 4.9 m/s is 5.214 W and the total generator power for 10 hours is 389.9 W. The energy produced is sufficient to light a 30-W lamp for 12 hours of use which will later be stored in a 12V 38 Ah capacity battery because the battery capacity used is 35.2 Ah with a battery efficiency of 85%.